2017
DOI: 10.1093/humrep/dex362
|View full text |Cite
|
Sign up to set email alerts
|

Surrogacy families headed by gay men: relationships with surrogates and egg donors, fathers’ decisions over disclosure and children’s views on their surrogacy origins

Abstract: Support was obtained from a Sapienza Starting Grant for Research to the first author (grant number AR11715C77EB56B2). None of the authors has any conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…9,10 In general, the participants had not been met with hostility or questioning that had affected their experiences of parenthood. This is in line with previous results indicating that heterosexual parents 17 Overall, the present findings are in line with previous results of both heterosexual parent 7 and gay father families, 20,21 where almost all parents had started telling the child about the surrogacy or planned to do so when the child was older. 17 However, parents following surrogacy have been found to be less open about the use of donor gametes 7 or about which of the fathers contributed his sperm, which supports the notion that there are layers of disclosure among donorconceiving families.…”
Section: Discussionsupporting
confidence: 94%
“…9,10 In general, the participants had not been met with hostility or questioning that had affected their experiences of parenthood. This is in line with previous results indicating that heterosexual parents 17 Overall, the present findings are in line with previous results of both heterosexual parent 7 and gay father families, 20,21 where almost all parents had started telling the child about the surrogacy or planned to do so when the child was older. 17 However, parents following surrogacy have been found to be less open about the use of donor gametes 7 or about which of the fathers contributed his sperm, which supports the notion that there are layers of disclosure among donorconceiving families.…”
Section: Discussionsupporting
confidence: 94%
“…Careaga (2011) claimed that in Mexico the majority of LG individuals with children, became parents in the context of a previous heterosexual relationship which is consistent with the existing international research (e.g., Patterson and Tornello, 2010 ; Tornello and Patterson, 2015 ). However, “a generational change in timing and pathways to parenthood is taking place” ( Tornello and Patterson, 2015 , p. 44), because younger LG individuals are having children after coming out, through sperm donation ( Lingiardi et al, 2016 ), surrogacy ( Blake et al, 2017 ; Carone et al, 2017 , 2018 ), adoption ( Goldberg, 2012 ), informal adoptions ( Amazonas et al, 2013 ), step parenting and co-parenting ( Tornello and Patterson, 2015 ; Carneiro et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, surrogates are integrated into an "elaborate web of procreative, father, and family identities" (Berkowitz & Marsiglio, 2007, p. 378). Recent scholarship has shown that the majority of gay men perceive their surrogacy relationships, from prepregnancy through to postbirth, as harmonious (Blake et al, 2016;Carone et al, 2017, Carone et al, 2018. Gay fathers have ongoing relationships with their surrogates, describing surrogates as extended family members and friends.…”
Section: Surrogacy Relationshipsmentioning
confidence: 99%